A well-posed multiscale regularization scheme for digital image denoising - Prasath, V.B. Surya (Zielona Góra: Uniwersytet Zielonogórski)
We propose an edge adaptive digital image denoising and restoration scheme based on space dependent regularization. Traditional gradient based schemes use an edge map computed from gradients alone to drive the regularization. This may lead to the oversmoothing of the input image, and noise along edges can be amplified. To avoid these drawbacks, we make use of a multiscale descriptor given by a contextual edge detector obtained from local variances. Using a smooth transition from the computed edges, the proposed scheme removes noise in flat regions and preserves edges without oscillations
Keywords: image restoration; edge-preserving; regularization; normalized local variance; adaptive parameter